Semi-active structural vibration control with magnetorheological damper based on hybrid fuzzy sliding mode controller - Zizouni, Khaled; Saidi, Abdelkrim; Fali, Leyla; Bousserhane, Ismail Khalil; Djermane, Mohamed (Institute of Advanced Engineering and Science, 2023)
Recently, structural vibration control has proved its capacity to save lives and keep structures safe during earthquakes. Furthermore, there is a wealth of research in both numerical and experimental studies. As a result, due to its simplicity and performance in mitigating structural vibrations generated by ground motions, semi-active control played a significant role in the majority of these studies. Nonetheless, the magnetorheological damper is the most often used semi-active device. In particular, the rheological fluid properties have gained adequate attention in earthquake energy dissipation and structural vibrations management, particularly in the civil engineering field. The semi-active control of three scaled excited structures is addressed in this study. A magnetorheological damper operated by a hybrid fuzzy sliding mode controller ensures the proposed control. However, to provide the appropriate current for the damper to operate, this proposed intelligent controller is combined with a clipped optimum algorithm. Otherwise, the numerical simulation results of the seismic excited scaled structure demonstrate the resilience of the suggested controller. As a result, four time-scaled seismic data are applied to the tested structure. Finally, the usefulness of the suggested semi-active control technique in mitigating earthquake structural vibration is demonstrated clearly in the compared controlled and uncontrolled responses.